PENGEMBANGAN MEDIA TORSO MATERI ORGAN PENCERNAAN MANUSIA UNTUK SISWA KELAS V SDN SATAK KABUPATEN KEDIRI TAHUN 2023-2024 - Nopiandari, Wulan; Sri Mujiwati, Endang; Sahari, Sutrisno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the results of the researcher's observations that in science learning about human digestive organs for class V students at SDN Satak, there was no learning media used by teachers regarding human digestive organs. When explaining the material, only use textbooks which contain unclear pictures. This has the effect that students are less interested and do not understand the material about human digestive organs so that the grades obtained by students are still below the KKM. The aim of this research and development is to determine the validity, practicality and effectiveness of torso media material on human digestive organs for fifth grade students at SDN Satak. This research uses the Research and Development (R&D) type of research with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. With the research subject being fifth grade students at SDN Satak Kec. Puncu District. Kediri. This research carried out a validation test to determine the validity of the media. Furthermore, there are two trial designs, namely a limited trial on 16 students and a wide trial on 17 students. The results of this research are: (1) Media validity obtained a media validation result of 93.33% which was declared very valid, material validation received a score of 90% which was declared very valid, and learning device validation obtained a score of 90.96% which was declared very valid. (2) Torso media on human digestive organs was declared practical by obtaining results from teacher response questionnaires of 100% and student response questionnaires of 96.8% limited trials, 99% extensive trials. (3) Torso media on human digestive organs was declared effective after limited trials by providing post-test questions, the results were 94.37% and extensive trials by providing post-test questions obtained 97.35% results, so that the digestive organ torso media can be said to be effective for use.